The effect of quality of the service upon customer satisfaction at royal safari garden resort and convention Cisarua Bogor - Dwi Gemina; Rully Zulkiply (STIE Binaniaga, 2019)
This research aims to analyze the impact of quality of the service upon customer satisfaction at Royal Safari Garden Resort and Convention Cisarua Bogor. The questionniares have been distributed to 100 respondents. Type of the research is descriptive and verificative one. The questionnaire has applied validity test, reliability test and classics assumption. Likert scale has been used before applying multiple regression test to see the effect of five independent variables upon one dependent variable. The result has indicated that simultaneously and partially quality service (physical evidence, emphaty, reliability, responsiveness and guarantee) has positively and significantly affected the Customers satisfaction at Royal Safari Garden Resort and Convention Cisarua Bogor. Keywords : Service Quality, Customer Satisfaction, Royal Safari Garden Resord and Convention Cisarua Bogor.